The BRICS—An Involuntary Contender Bloc Under Attack - Van der Pijl, Kees (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2017)
In this piece I look at the BRICS bloc (Brazil, Russia, India, China, and South Africa) as rivals of the West, united more by circumstance than by intent. It emerged as a seemingly innocuous banker’s gimmick referring to the ‘emerging market’ potential of the countries thus thrown together, but due to the aggressive Western response to independent policies, the BRICS have slowly moved towards solidifying their cohesion. Comprising half the world’s population, the bloc on the eve of the financial crisis of 2008 was closing in on the West. In Purchasing Power Parity (PPP) terms, China’s GDP was three-quarters the size of the US economy, and India no. 4 behind Japan, whilst Brazil and Russia were catching up with the main EU states (Armijo 2007: 12). The 2008 financial collapse in the West contracted China’s export markets and speculation that the BRICS were passé, was rife (Sharma, 2012: 6). However, China and India soon recovered, surpassing the US and Japan, respectively, whilst Russia and Brazil are trailing just behind Germany (World Bank 2016). This (uneven) recovery of the BRICS bloc in turn has provoked an even less benevolent response, increasingly amounting to a straightforward confrontation policy. My argument is that once the crisis forcedChina, the bloc’s locomotive, to slow down and the global commodity boom ended, a Western strategy of isolating it from the other BRICS ensued. This is most obvious in the case of the NATO siege on Russia.